2007
DOI: 10.1093/toxsci/kfm179
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Tissue Levels of 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD), mRNAs, and Toxicity in the Developing Male Wistar(Han) Rat

Abstract: We compared the effects of a single acute dose, or chronic fetal exposure, to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) on the male reproductive system of the Wistar(Han) rat. Tissue samples were taken from dams on gestation day (GD)16 and GD21, and from offspring on postnatal days (PND)70 and 120. Steady-state concentration of TCDD was demonstrated in the chronic study: body burdens were comparable in both studies. Fetal TCDD concentrations were comparable after acute and chronic exposure, and demonstrate mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…It is also appears that adverse effects in prenatal rats appear to occur from exposure during a relatively short time window (SCF 2001). Bell et al (2007aBell et al ( , 2007bBell et al ( , 2007c) also compared an acute exposure with a chronic exposure in pregnant rats and confirmed that an acute exposure results in relatively higher exposure of the foetus. However, in these studies the chronic exposure resulted in a delayed puberty in male off-spring at much lower doses than in the pups of mothers exposed to a single high dose.…”
Section: Risk Assessmentmentioning
confidence: 79%
See 1 more Smart Citation
“…It is also appears that adverse effects in prenatal rats appear to occur from exposure during a relatively short time window (SCF 2001). Bell et al (2007aBell et al ( , 2007bBell et al ( , 2007c) also compared an acute exposure with a chronic exposure in pregnant rats and confirmed that an acute exposure results in relatively higher exposure of the foetus. However, in these studies the chronic exposure resulted in a delayed puberty in male off-spring at much lower doses than in the pups of mothers exposed to a single high dose.…”
Section: Risk Assessmentmentioning
confidence: 79%
“…The levels of 50, 100 and 200 pg TEQ g -1 , used for the assessment, however, may be a clear underestimation, because higher levels were found in the index loin (433 pg TEQ/g) and also the pooled samples in The Netherlands indicated higher individual levels (around 300 pg TEQ g -1 fat). Moreover, the high levels in the meat also pointed to the possibility of high levels in the liver, an effect well-known in rats exposed to high levels of dioxins (Hurst et al 2000a, Bell et al 2007c. Own data in pork from one of the latest dioxin incidents showed e.g.…”
Section: Risk Assessmentmentioning
confidence: 91%
“…in Kandori et al (2005). Also, markedly unbalanced sample sizes may occur, e.g., n i = 42,...,74 in Bell et al (2007). For this reason, we investigated a number of unbalanced situations (Tables 6 and 7).…”
Section: Parameter Settingsmentioning
confidence: 99%
“…Total RNA from H4-II-E cells and MCF-7 cells was isolated, quantitated and 50 ng was reverse transcribed into cDNA and quantitative RT-PCR analysis performed essentially as described (Bell et al, 2007), except that confluent cultures were lysed with 0.2 ml of lysis buffer and the amount of cDNA used for multiplex PCRs was 2 ng. PCR efficiencies were empirically determined for each probe, and varied from 109-118% for rat genes and from 110-125% for human genes.The cDNA sequences of the human CYP1A1, -actin and AhR are listed in Table 2.…”
Section: Rna and Rt-pcr Analysismentioning
confidence: 99%
“…The induction of CYP1A1 RNA is a highly sensitive marker of AhR activation (Bell et al, 2007), and measurement of CYP1A1 RNA provides a quantitative measure of AhR activation, that is arguably superior to measuring P450 protein activity, since effects such as regulation of translation, or inhibition of enzyme activity, can vitiate interpretation, and the effects of compound metabolism can be minimised by measuring response at an early time point. This assay thereby enables a quantitative comparison between agonistic and antagonistic activities of AhR ligands.…”
Section: /2/09 Page 13mentioning
confidence: 99%